2019
DOI: 10.1111/codi.14584
|View full text |Cite
|
Sign up to set email alerts
|

A cohort study of local excision followed by adjuvant therapy incorporating a contact X‐ray brachytherapy boost instead of radical resection in 180 patients with rectal cancer

Abstract: Aim Recent data have suggested near‐equivalent oncological results when treating early rectal cancer by local excision followed by radio‐ ± chemotherapy rather than salvage radical surgery. The aim of this retrospective study was to assess the use of contact X‐ray brachytherapy within this paradigm. Method All patients had undergone local excision and were referred to our radiotherapy centre for treatment with contact X‐ray brachytherapy. Postoperative (chemo)radiotherapy was also given in their local hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…However, after LR failure, the highest 5-year survival rate of patients receiving remedial surgery is only 58% (21)(22)(23). The latest research shows that AT can achieve the same long-term prognosis as remedial surgery (24). Compared with remedial surgery, AT has advantages in trauma and postoperative complications and can eliminate subclinical lesions so as to improve the local control rate.…”
Section: Discussionmentioning
confidence: 99%
“…However, after LR failure, the highest 5-year survival rate of patients receiving remedial surgery is only 58% (21)(22)(23). The latest research shows that AT can achieve the same long-term prognosis as remedial surgery (24). Compared with remedial surgery, AT has advantages in trauma and postoperative complications and can eliminate subclinical lesions so as to improve the local control rate.…”
Section: Discussionmentioning
confidence: 99%
“…In observational studies reporting W&W strategies the local recurrence rate varies between 5% and 60% and the metastases rate between 6% and 30% being more elevated in cases of local recurrence (21). In elderly and comorbid patients the competing effects of oncological and surgical risk may argue in favor of a W&W approach as a safe alternative (23) Estimation of conditional survival using the large IWWD (international Watch and Wait Database) in 768 patients has suggested that after sustained cCR for 3 years the risk of late local recurrence does not exceed 5% (22) Smith compared 136 patients with RP-TME and ypCR after nCRt and 113 patients with cCR and W&W. At 5 years overall survival was 73% in W&W vs 94% in ypCR with a higher rate of distant metastasis in W&W (21). In the OPRA study a NOM was possible in up to 60% of patients with no 3-year Disease-Free-Survival difference when compared with historical series (4).…”
Section: Discussionmentioning
confidence: 99%
“…Estimation of conditional survival using the large IWWD (international Watch and Wait Database) in 768 patients has suggested that after sustained cCR for 3 years the risk of late local recurrence does not exceed 5% [22] …”
Section: Discussionmentioning
confidence: 99%
“…Patients that have undergone excision of malignant polyps can also be offered CXB +/- EBRT to decrease the risk of local regrowth, level 2b [24] . Patients with low-risk (see Table 2 ) incompletely excised or close margins pT1 tumours following local excision (R1 resection) can have CXB to the tumour site if they are not fit for further surgery.…”
Section: Patient Selectionmentioning
confidence: 99%